Promoting customer loyalty through e-marketing communication at commercial banks - Anh, Nguyen Quoc; Sang, Tang My; Pham, Duong Phuong Thao (Nurture, 2023)
Purpose: The research aims to find out the relationship between e-marketing communication, customer satisfaction, and loyalty at Vietnamese commercial banks. Design/Methodology/Approach: Customers who use e-banking services in Ho Chi Minh City are surveyed to gather the data. Using Google Forms, the survey was first pretested on 10 people. There were 224 valid responses to the official survey. Following that, SmartPLS processed the data in two steps: evaluating the measurement model and the structural model. Findings: The results show that e-marketing communication has a positive relationship with customer satisfaction and loyalty. Besides, customer satisfaction mediates a positive relationship between e-marketing communication and customer loyalty. Conclusion: The outstanding advancement of information technology has facilitated digital transformation in all aspects of life, including the banking industry. As technology advanced, marketing was the industry that underwent the most change. E-marketing makes it possible to establish and maintain a close relationship with clients, which is essential for being successful in luring them. E-marketing must connect many people, particularly the target customer group, and is not just focused on the design, logo, and overall user interface. Research Limitations and Implications: The effectiveness of direct marketing is not combined or compared in this study. It only examines the effect of e-marketing. Practical Implications: The banks should identify, contact, and maintain regular contact with potential customers. They can incorporate unstructured data from social networks. Furthermore, the banks must develop methods for evaluating and measuring the efficacy of their marketing efforts. This study gives bank managers in Vietnam suggestions for an appropriate e-marketing strategy.